The Impact of Media and Technology in Christian Religious Education Strategy - Resiani Simamora (Asian Journal of Philosophy and Religion, 2023)
This research aims to describe the impact of media and technology in Christian Religious Education strategies. This impact is to build social change and to convey messages from God. Media is a communication tool in the form of graphic, photographic and electronic tools to capture, process and reconstruct visual or audio information. Technology is the practice of knowledge in the form of useful tasks to increase effectiveness and efficiency. Christian religious education is not against developments in media and technology. The background of this article is the impact of media and technology on Christian Religious Education strategies. The research method used is descriptive qualitative research. The result of this article is that media and technology in Christian religious education strategies have an impact on building social change and conveying God's message.